Charged-Particle Ratios and Large-Transverse-Momentum-Dependent Quark Statistics - Liang, Thow Yick (Institutional Knowledge at Singapore Management University, 1982)
The concept of leading quarks is developed and incorporated into the quark statistics. This gives the quark statistical model large-pT-dependent characteristics and is able to explain the variation of the ratios of charged particles emitted over a wide range of large pT during violent collisions. This feature is clearly manifested when the data obtained by the Chicago-Princeton Collaboration for ?-p, pp, and p``n'' collisions at 300 and 400 GeV in the pT range of 0.77 to 6.91 GeV/c are analyzed.